Variation in Structure and Density within a Single Tree of Michelia champaca Linn. - Purkayastha, S. K.; Lal, Krishna; Ramesh Rao, K.; Negi, G. S. (Indian Forester, 1974)
Variation in anatomical structure and density has been studied in the main hole of a 25 year old tree of Michelia champaca grown at Newforest, Dehra Dun. For studying the variation from pith to periphery, consecutive blocks comprising 2-3 rings were taken along one radius and at two heights. For variations from bottom to top, two growth sheaths were investigated at eight levels. All anatomical data except fibre length were collected from cross sections by the point sampling method. There is no evidence of any consistent pattern in the variation in anatomical structure within the tree. However the fibre length shows a tendeney to increase from the pith outwards and to decrease from the bottom upwards though the trend in both cases is somewhat irregular. Density values within the tree also show a similar irregular trend. Both anatomical structure and density on the whole vary within rather narrow limits within a growth sheath except near the ground level. Study of the correlation between anatomical structure and density has shown that wall thickness, diameter and length of fibres account for 77 per cent of the variation in density. The proportion of fibres appears to have no significant effect on density.